Anti-Bacterial Effect and Cytotoxicity Assessment of Lipid 430 Isolated from Algibacter sp. - Schneider, Yannik Karl-Heinz; Østnes Hansen, Kine; Isaksson, Johan; Ullsten-Wahlund, Sara Maria; Hansen, Espen; Andersen, Jeanette Hammer (Molecules, 2019)
Two bacterial isolates from the Barents Sea, both belonging to the genus Algibacter , were found to yield extracts with anti-bacterial bioactivity. Mass spectrometry guided dereplication and purification of the active extracts lead to the isolation of the same active principle in both extracts. The structure of the bioactive compound was identified via mass spectrometry and nuclear resonance spectroscopy and it turned out to be the known lipopeptide Lipid 430. We discovered and determined its previously unknown anti-bacterial activity against Streptococcus agalactiae and revealed a cytotoxic effect against the A2058 human melanoma cell line at significantly lower concentrations compared to its anti-bacterial concentration. Flow cytometry and microscopy investigations of the cytotoxicity against the melanoma cell line indicated that Lipid 430 did not cause immediate cell lysis. The experiments with melanoma cells suggest that the compound functions trough more complex pathways than acting as a simple detergent.